A Simple Chemical Synthesis of Sugar Nucleoside Diphosphates in Water. Issue 1 (16th February 2018) - Tanaka, Hidenori; Yoshimura, Yayoi; Hindsgaul, Ole
Abstract: Chemoenzymatic oligosaccharide synthesis is attractive since it eliminates the tedious multistep protection‐deprotection requirements of pure chemical synthesis. Chemoenzymatic synthesis using glycosyltransferases, however, requires not only the correct enzyme to control both regio‐ and stereospecificity, but also the glycosyl donor to provide the sugar that is added. This unit describes a simple synthesis of sugar‐nucleoside diphosphates (sugar‐NDPs), the type of glycosyl donor (e.g., UDP‐Glc, UDP‐Gal, ADP‐Glc) required by most glycosyltransferases, by using a chemical coupling reaction in water. The preparation of sugar‐NDPs by this method therefore does not require any skills in synthetic organic chemistry. Curr. Protoc. Nucleic Acid Chem . 54:13.12.1‐13.12.10. © 2013 by John Wiley & Sons, Inc.